Mirador II – A Monitoring and Management Tool for the SPP3 - Trindade Jr., Onofre; Carmo, Maxweel Silva; Ribeiro, Rômulo Eugênio (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41214, 2000)
The application of workstation clusters as a parallel machine has been of widespread use. Althrough highly cost-effective, the ease of use of such systems can be improved with the utilization of monitoring and management tools. The Mirador II was developed to make easy the user interaction with the SPP3, a parallel architecture that provides high computational power at low cost using commonly avaliable hardware components. User account management, cluster resources monitoring, management and monitoring of running processes, Myrinet network monitoring, parallel machine autonomous managemnt and Internet interface are among its main features. The Mirador II can be also employed, with minor configuration, as a monitoring and management tool for workstation clusters. The daily use of the Mirador II on the SPP3 have shown its usability, making common tasks much easier to accomplish by inexperienced Unix users.